Rhamnolipids know-how: Looking for strategies for its industrial dissemination - Lovaglio, R. B. [UNESP]; Silva, V. L. [UNESP]; Ferreira, H. [UNESP]; Hausmann, R.; Contiero, J. [UNESP] (Elsevier B. V., 2015)
Despite the numerous advantages of biosurfactants, such as low toxicity, biodegradability and high stability, these compounds are not widely used because of the high cost of production. Details about genetics, regulation and biosynthesis of rhamnolipids by Pseudomonas aeruginosa, are extremely important to the development of bioprocesses involving the synthesis of these compounds. The holding of such knowledge associated with the use of metabolic engineering tools allow modification of producing strains and the development of synthetic routes, with the purpose of increasing the production of rhamnolipids. Considering the need to obtain this know-how, this review provides information on the rhamnolipids, covering genetics, biosynthesis of hydrophobic and hydrophilic portions, and regulation, plus some future strategies that would contribute to the expansion of the production of this green surfactant.
Keywords: Biosynthesis; Metabolic pathways; Regulation; Rhamnolipids; De novo synthesis; Β-oxidation